Pengaruh Kompres Daun Kubis Terhadap Penyembuhan Pembengkakan Payudara pada Ibu Nifas di Wilayah Kerja Puskesmas Jiput - Veny Suci Meilawati; Ita Herawati (Malahayati Nursing Journal, 2023)
ABSTRACT Breast swelling is an unpleasant physiological condition characterized by swelling and pain in the breasts that occurs due to an increase in breast milk volume. It is reported that in the last three years (2019-2021) cases of breast swelling in breastfeeding mothers at the Jiput Health Center have increased with an average percentage of cases of 15.11% per year. It is known the effect of cabbage leaf compresses on healing breast swelling in postpartum mothers at the Jiput Health Center Working Area, Pandeglang Regency in 2022. The research method uses quasi-experiments with a pre-posttest two group design. Sample of this study was 30 puerperal mothers who experienced breast swelling with sampling technique uses simple random sampling. Instruments use questionnaires. Bivariate analysis uses the paired t- test and independent t-test.The average breast swelling scale in the intervention group before being given cabbage leaf compresses was 5.20 and after being given cold cabbage leaf compresses decreased to 1.93, while in the control group before being given warm water compresses was 5.13 and after being given warm water compresses decreased to 3.07. The results of statistical tests showed that there was an effect of comparing cabbage leaf compresses with warm water on the healing of breast swelling (p = 0.000). Applying cabbage leaf compresses is more effective at curing breast swelling compared to applying warm water compresses. It is expected in puerperal mothers in dealing with breast swelling problems to carry out herbal complementary therapy actions, one of which is by doing cold cabbage leaf compresses on the breasts. Keywords: Breast Swelling, Cabbage Leaf Compresses, Warm Water Compresses  ABSTRAK Pembengkakan payudara merupakan kondisi fisiologis yang tidak menyenangkan ditandai dengan bengkak dan nyeri pada payudara yang terjadi karena peningkatan volume ASI. Dilaporkan dalam tiga tahun terakhir (2019-2021) kasus pembengkakan payudara di Puskesmas Jiput meningkat dengan rata-rata kasus 15,11% per tahun.Diketahuinya pengaruh kompres daun kubis terhadap penyembuhan pembengkakan payudara pada ibu nifas di Wilayah Kerja Puskesmas Jiput Kabupaten Pandeglang tahun 2022.Metode penelitian menggunakan quasi eksperiment dengan desain two group pre- posttest. Sampel penelitian ini adalah ibu nifas yang mengalami pembengkakan payudara sebanyak 30 orang. Teknik pengambilan sampel menggunakan simple random sampling. Instrumen penelitian menggunakan kuesioner. Analisis bivariat menggunakan uji paired t-test dan independent t-test. Rata-rata skala pembengkakan payudara pada kelompok intervensi sebelum diberikan kompres daun kubis adalah 5,20 dan sesudah diberikan kompres daun kubis dingin menurun menjadi 1,93, sementara pada kelompok kontrol sebelum diberikan kompres air hangat adalah 5,13 dan sesudah diberikan kompres air hangat menurun menjadi 3,07. Hasil uji statistik menunjukkan terdapat pengaruh perbandingan kompres daun kubis dengan air hangat terhadap penyembuhan pembengkakan payudara (p = 0,000). Pemberian kompres daun kubis lebih efektif menyembuhkan pembengkakan payudara dibandingkan dengan pemberian kompres air hangat. Diharapkan pada ibu nifas dalam menangani masalah pembengkakan payudara untuk melakukan tindakan terapi komplementer herbal salah satunya dengan melakukan kompres daun kubis dingin pada payudara. Kata Kunci: Pembengkakan Payudara, Kompres Daun Kubis, Kompres Air Hangat